Choosing to live how to defeat suicide through cognitive therapy - Ellis, Thomas E.; Newman, Cory Frank (Oakland, CA New Harbinger Publications, 1996)
Counter Choosing to Live is the first self-help guide addressed to those who are considering suicide. In an empathetic nonjudgmental tone, the authors provide tools to help readers assess the risk and understand the factors that reinforce suicidal talk and behaviors. A step-by-step program for change shows how to replace negative beliefs and develop alternative skills for solving problems. For professionals who are helping seriously depressed clients, Choosing to Live offers the clear guidance of a treatment manual plus readings and exercises for clients to do at home.
Suicide is an ugly word -- Are you a suicidal person? -- What's wrong with you? (what makes people suicidal) -- Not so fast maybe you don't need to change -- Step one: survive the crisis -- Step two: know thyself (thinking and feeling) -- Step three: where goes the head, the rest will follow: you can change how you think (and feel) -- Step four: feeling better through coping (sometimes accommodation is okay) -- Step five: solve your problems without dying -- Other skills to enhance your life -- It's okay to get flowery about life.
Includes bibliographical references (pages 183-185) and index.
Keywords: Cognitive therapy; Suicidal behavior; Suicide -- Prevention; Cognitive Therapy; Suicide -- prevention & control